About the problem of selecting models for production line - Pihnastyi, O. M.; Bondarenko, K. M. (Бердянський університет менеджменту і бізнесу, 2016)
The article presents comparative characteristic of models of industrial production lines operating in transition mode, their advantages and disadvantages are analyzed. For these models the accuracy of calculations of aggregated parameters of industrial production lines is evaluated. The principle of the PDE-models is showed using the statistical theory of describing production systems. The prospects of developing models of industrial production lines that are used in the design of in-line production control systems.

У статті наведено порівняльну характеристику моделей промислових виробничих ліній, що функціонують в перехідному режимі, проаналізовано їх переваги та недоліки. Для розглянутих моделей оцінена точність розрахунків агрегованих параметрів промислових виробничих ліній. Показано принцип побудови PDE-моделей з використанням статистичної теорії опису виробничих систем. Обґрунтовано перспективи розвитку моделей виробничих потокових ліній, які використовуються при проектуванні систем управління потоковим виробництвом.
Keywords: models of production processes; production line transition mode; PDE-model; model of statistical dynamics; control systems; моделі виробничих процесів; перехідний режим; поточні лінії; PDE-модель; системи управління; моделі статистичної динаміки